KERUSAKAN INSANG DAN PERTUMBUHAN UDANG WINDU (PENAEUS MONODON FAB.) DI TAMBAK KEPUTIH SURABAYA YANG TERCEMAR LOGAM TIMBAL (PB) - UMAMI, FAUZIATUL (Universitas Negeri Surabaya, 2012)
Keputih Surabaya is a coastal area that most of people livelihood as farmers. Tiger shrimp (Penaeus monodon Fab.) is one of the organisms are cultivated in fishponds Keputih Surabaya. That fishponds has been known contaminated by lead (Pb). One of the lead (Pb) entry mechanisms into the shrimp is through the gills. Therefore, needs to be seen shrimp gill damage caused by the lead (Pb) metal. This research conduct to determine levels of lead (Pb) in water, sediment and tiger shrimp, gill damage and the growth of shrimp in fishponds that is contaminated by lead (Pb). This research is the observation that take samples from 3 stations. Each station is taken water, sediment, and tiger shrimp (Penaeus monodon Fab.). To determine the levels of lead (Pb) is used Analysis Atomic Absorption (AAS) method at Balai Besar Teknik Kesehatan Lingkungan dan Pemberantasan Penyakit Menular (BTKL) Surabaya Laboratory. Tiger shrimp gill preparations made by the method of preservation microtehnique Haematoxylin-Eosin staining in the Pathology Laboratory Airlangga University, Surabaya. The data that is obtained were analyzed descriptively and compared with the quality standards based on Government Regulation no. 82 of 2001 about Water Quality and Water Pollution Control. The results showed levels of Pb in the water 0,1903 ppm and 5,146 ppm sediment, those results exceed the quality standards (> 0,03 ppm), and 6,6104 ppm in tiger shrimp exceeds the quality standard (> 0,5 ppm). Gill damage exposure lead (Pb) is necrosis, congestion and rupture secondary filaments. Tiger shrimp growth is inhibited, because adult shrimp reaches length is 33 cm and weight 20-35 grams. Keputih Surabaya fishpond water quality except temperature and pH are not in accordance with requirements of growth and development of the shrimp.